Narrativas da minha constituição docente na educação infantil : o brincar e a escuta das crianças durante a pandemia - Souza, Genilda Nascimento de (2021)
This Master's research was developed with the Graduate Program in Education of the Federal University of Mato Grosso, Ctompus University of Rondonópolis (PPGEdu/UFMT/CUR) in the Line of Research Childhood, Youth and Contemporary Culture: rights, policies and diversity, under the guidance of Profa. Dr. Elni Elisa Willms. Yousee it as the main objective to reflect on the experiences of the research teacher, narrating facts from her childhood and intertwining them with a life story, which led to her becoming a teacher of early childhood education. The theme was the autobiographical narrative of a kindergarten teacher. We opted for the autobiographical research, of a qualitative nature, welcoming the narratives of itself as an instrument of data collection, following the reflection on aspects of play, because it is the main guide axis of the pedagogical practices of Early Childhood Education. The narratives of their life stories confronted with experiencesand knowledge were chosen, turning toknowing that they are transformedor in teaching practices in early childhood education. It was concluded that the stories constitute the subject, through andwithout the experiences and experiencesand influence the formationof character, personal and professional formation, as well as allow reflections, although reflecting on such experiences is a subjective choice. In the course of this research, the challenges of being a teacher in times of pandemic caused by Covid-19, if before the path was arduous, now other problems are faced such as the on-line and appropriate methodologies and their interaction to learn new educational resources that personalize the teaching in times of pandemic.